(untitled) (Bangladesh Journal of Botany, 2010)
GC-MS analysis of essential oil of Blumea balsamifera (L.) DC. leaf revealed the presence of 50 components, contributing to 99.07% of the oil. The dominant components in the oil from leaves were borneol (33.22%), caryophyllene (8.24%), ledol (7.12%), tetracyclo[6,3,2,0,(2.5).0(1,8) tridecan-9-ol, 4,4-dimethyl (5.18%), phytol(4.63%), caryophyllene oxide(4.07%), guaiol (3.44%), thujopsene-13 (4.42%), dimethoxydurene (3.59%) and γ-eudesmol (3.18%). Key words: Blumea balsamifera; Essential oil; Volatile oil; Chemical components DOI: 10.3329/bjb.v38i1.5132 Bangladesh J. Bot. 38(1): 107-109, 2009 (June)